PEMBENTUKKAN KARAKTER PESERTA DIDIK MELALUI PEMANFAATAN LAGU ANAK-ANAK DI KELOMPOK BERMAIN FLAMBOYAN DESA KOTA BANGUN III KECAMATAN KOTA BANGUN KABUPATEN KUTAI KARTANEGARA PADA TAHUN AJARAN 2016/2017 - Rawin - Rawin; Mahkamah - Brantasari (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2018)
Shaping child character is an important aspect during the process of early childhood development. One of learning method that encourage child character is by using songs for children to create fun learning atmosphere that gets rid of boredom frustration. As the consequence, the researcher conducted a classroom action research to shape better child character through the usage of songs for children. Moreover, the research was conducted in Flamboyan Playgroup in Desa Kota Bangun III Kecamatan Kota BangunKabupatenKutaiKartanegara.In addition, to collect the data, the researcher employed teacher and students observation sheet and documentation. The research subjects were twenty five students. To analyze the data, the researcher applied descriptive analysis with qualitative approach.The result of the research shows that students’ character has improved after learning with child songs. Since, at the early cycle, students’ character developed 25%. Meanwhile, after implementing child songs, the character developed into 85%, which met the research target. Moreover, the teacher felt easier to deliver moral value through songs since the students felt happy during learning.